2019
DOI: 10.1177/1071100719863711
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of Opioid Use After Adoption of a Prescribing Guideline for Outpatient Foot and Ankle Surgery

Abstract: Background: In 2016, our provider group adopted an initial prescription opioid maximum guideline to reduce overprescription of opioids. The purpose of this study was to prospectively assess opioid consumption patterns following implementation of this guideline in patients undergoing outpatient foot and ankle surgery. Methods: Over a 1-year period, we prospectively analyzed opioid prescription and use patterns of 303 consecutive patients. Opioid consumption was verified by pill counts completed at the 2- and 6-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Similarly, this study had a lack of a definitive consensus on prescribing opioid analgesics for moderate acute postoperative pain, however, the consensus to use opioids at more severe pain levels in this study is reflective of the literature. These include a level II prospective observational cohort study that proposed patients who had hindfoot, ankle, or osseous procedures required more opioids [ 9 ], as well as the study by Chan et al that found fewer opioids were required postoperatively for percutaneous foot and ankle surgery due to the smaller incisions and minimal disruption to surrounding soft tissue [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, this study had a lack of a definitive consensus on prescribing opioid analgesics for moderate acute postoperative pain, however, the consensus to use opioids at more severe pain levels in this study is reflective of the literature. These include a level II prospective observational cohort study that proposed patients who had hindfoot, ankle, or osseous procedures required more opioids [ 9 ], as well as the study by Chan et al that found fewer opioids were required postoperatively for percutaneous foot and ankle surgery due to the smaller incisions and minimal disruption to surrounding soft tissue [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our patients, closely following the postoperative protocol did not need to resort to opioid use, which is reported to be greater in chronic pain patients due to tolerance, dependence and opioid-induced hyperalgesia [ 59 ]. For these reasons, orthopaedic surgeons should be aware that long-term postoperative opioid use must be avoided [ 59 ], as its inadvertent overprescription may place patients and their communities at risk of abuse or OUD [ 58 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…12 14 Additionally, almost half of the prescribed opioid pills are not used which are at risk of misuse. 12 24 25 26 27 To address this, 32 States in the United States have enforced legislation which limits opioid prescriptions to a 7-day supply or less. However, further prescription guidelines are needed to optimize pain management: creating parameters based on specific patient characteristics along with patient education in a multidisciplinary approach.…”
Section: Discussionmentioning
confidence: 99%